2011
DOI: 10.1002/jnr.22821
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of dopamine D3 receptors in modulating methamphetamine‐induced behavioral sensitization and ultrastructural plasticity in the shell of the nucleus accumbens

Abstract: Persistent changes in behavior and psychological function that occur as a consequence of exposure to drugs of abuse are thought to be mediated by the structural plasticity of specific neural circuits such as the brain’s dopamine (DA) system. Changes in dendritic morphology in the nucleus accumbens (NAc) accompany druginduced enduring behavioral and molecular changes, yet ultrastructural changes in synapses following repeated exposure to drugs have not been well studied. The current study examines the role of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 52 publications
4
41
0
Order By: Relevance
“…However, acute injection of YQA14 prior to METH administration significantly inhibited METHinduced hyperactivity, suggesting a reduction in METH reward and psychomotor-stimulation. This is consistent with the significantly attenuated acute locomotor responses observed following administration of METH in D 3 R −/− mice compared with the effects observed in wild-type mice [30] . These results are also consistent with the ability of YQA14 and other D 3 R antagonists, such as SB-277011A, NGB2904, and PG-01037, to significantly inhibit METH or cocaine selfadministration [12,13,18,21,22,[31][32][33][34] and METH-or cocaine-enhanced electrical brain stimulation rewards, two of the other most common animal models used to evaluate drug reward systems [14-16, 22, 33, 35] .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, acute injection of YQA14 prior to METH administration significantly inhibited METHinduced hyperactivity, suggesting a reduction in METH reward and psychomotor-stimulation. This is consistent with the significantly attenuated acute locomotor responses observed following administration of METH in D 3 R −/− mice compared with the effects observed in wild-type mice [30] . These results are also consistent with the ability of YQA14 and other D 3 R antagonists, such as SB-277011A, NGB2904, and PG-01037, to significantly inhibit METH or cocaine selfadministration [12,13,18,21,22,[31][32][33][34] and METH-or cocaine-enhanced electrical brain stimulation rewards, two of the other most common animal models used to evaluate drug reward systems [14-16, 22, 33, 35] .…”
Section: Discussionsupporting
confidence: 87%
“…The experimental results observed in the present study are also consistent with findings in studies of other D 3 R antagonists (ie, nafadotride, U99194A and GR103691) that have shown that blockade of D 3 Rs attenuates the behavioral sensitization produced by repeated amphetamine administration [42,43] . The D 3 receptor mutant (D 3 R −/− ) mice also exhibited attenuated acute locomotor responses as well as the development of behavioral sensitization to METH compared with the results in wild-type mice [30] . Taken together, these results suggest an important role for D 3 Rs in METH-induced locomotor sensitization and possibly in relapse toward METH-seeking behavior.…”
Section: Discussionmentioning
confidence: 95%
“…The METH injection paradigm used in this study has been demonstrated in previous studies to produce robust locomotor sensitization4748. Mice were given once-daily injections of saline for two consecutive days (day 1-2), after which they were randomly grouped into two.…”
Section: Methodsmentioning
confidence: 99%
“…D3R −/− mice have been previously described (Zhu et al, 2012). D3R −/− mice and control WT mice were bred under specific pathogen-free conditions in the same room of our animal facility.…”
Section: Animalsmentioning
confidence: 99%
“…For example, a recent study showed that inhibition of the dopamine D3R attenuated the rewarding and incentive motivational effects of METH in rats (Chen et al, 2014). Our previous study showed that the D3R plays distinct roles in modulating METH-induced behavioural sensitization (Zhu et al, 2012). Therefore, D3Rs may be potential targets for the treatment of METH dependence (Higley et al, 2011;Tziortzi et al, 2011).…”
Section: Introductionmentioning
confidence: 97%